Soil chemical properties influences on the growth performance of Eucalyptus urophylla planted in dryland ecosystems, East Nusa Tenggara - Ronggo Sadono; Wahyu Wardhana; Pandu Yudha Adi Putra Wirabuana; Fahmi Idris (Journal of Degraded and Mining Lands Management, 2021)
Understanding the relationship between soil chemical characteristics and forest productivity is importantly required to support sustainable forest management, mainly in eucalyptus plantation. This study investigated the influence of soil chemical properties on the growth performance of Eucalyptus urophylla which established in dryland ecosystems, East Nusa Tenggara. Forest inventory was undertaken by N-trees sampling in the priority locations for E. urophylla development, located in Buat, Fatukoto1, and Fatukoto2. Four parameters were selected to describe the growth performance of E. urophylla, comprising diameter, height, volume, and mean annual increment. In each sampling point, soil sample was collected at the depths of 0-10, 11-20, and 21-30 cm. Then, the sample was composited before brought to the laboratory for quality analysis. Six parameters were selected to quantify the soil chemical characteristics, namely soil acidity (pH), soil organic carbon (SOC), total nitrogen (TN), available phosphorus (Av-P), exchangeable potassium (Exc-K), and cation exchange capacity (CEC). Results found that soil chemical properties from three locations were significantly different in pH, SOC, Av-P, and CEC. However, this study recorded the content of TN and Exc-K were statistically equal among the three sites. Difference soil chemical properties were also followed by the variation growth of E. urophylla, particularly in diameter and height. The highest volume of eucalyptus stand was observed in Fatukoto1 (181.06+95.46 m3 ha-1), followed by Buat (142.67+27.19 m3 ha-1) and FatukotoII (99.09+62.46 m3 ha-1). There were four soil parameters that meaningfully affected the growth performance of E. urophylla, i.e. pH, Av-P, Exc-K, and CEC. Among those parameters, Av-P demonstrated a consistent effect on the growth performance of E. urophylla. According to these findings, this study concluded that Av-P substantially provided higher effect on the growth performance of E. urophylla than other soil chemical parameters.